High-temperature-resistant neodymium-iron-boron magnet and preparation method thereof

CN123017665APending Publication Date: 2026-10-30JIANGSU RANO MAGNETICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611475297.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

本发明采用层状复合氧化物改性粉体与硼氧复合改性粉体协同复配,有效改善传统钕铁硼磁体高温稳定性差与物料混合不均的缺陷。其中,层状复合氧化物改性粉体经高温煅烧脱羟基后具有稳定的多孔层状结构与高比表面积,在混料阶段可通过表面吸附作用有效促进硼氧复合改性粉体在钕铁硼基体粉末中的均匀分散,改善各组分颗粒间的润湿性与接触均匀性;硼氧复合改性粉体在烧结过程中均匀分布于晶界区域,可显著优化磁体晶界结构、强化晶界稳定性,有效抑制高温下磁畴翻转与晶粒恶化行为。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017665A_ABST
    Figure CN123017665A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of permanent magnet material preparation, in particular to a high-temperature-resistant neodymium-iron-boron magnet and a preparation method thereof. The preparation method comprises the following steps: mixing and press-molding neodymium-iron-boron powder, boron-oxygen composite modified powder and layered composite oxide modified powder to obtain a blank through two-stage sintering and two-stage tempering and cooling, and then performing finishing processing to obtain a finished product. Through the synergistic compounding of the layered composite oxide modified powder and the boron-oxygen composite modified powder, the defects of poor high-temperature stability of traditional neodymium-iron-boron magnets and uneven material mixing are effectively improved, the high-temperature coercive force is significantly improved, the high-temperature irreversible magnetic loss is reduced, the thermal stability and the thermal shock resistance are enhanced, and the use stability and service life under high-temperature and high-load severe working conditions are greatly improved, so that the application meets the use requirements of new energy automobile driving motors, high-temperature servo motors and industrial high-temperature permanent magnet devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of permanent magnet material preparation technology, specifically to a high-temperature resistant neodymium iron boron magnet and its preparation method. Background Technology

[0002] Neodymium iron boron (NdFeB) permanent magnets are widely used in new energy motors, industrial servo equipment, and high-end permanent magnet devices due to their excellent energy product, coercivity, and comprehensive magnetic properties. As high-end equipment gradually evolves towards high-load, high-speed, and high-temperature operating conditions, more stringent technical requirements are being placed on the thermal stability and high-temperature demagnetization resistance of NdFeB magnets.

[0003] Currently, the production process of conventional NdFeB products on the market is mature and stable, with a high degree of industrialization, and can well meet the usage requirements under normal ambient temperature conditions. However, due to the limitations of the material itself, coupled with the industry's traditional single modification and optimization methods, the performance improvement space of the products is relatively limited. This leads to conventional NdFeB magnets being prone to magnetic performance decay and significant thermal demagnetization in high-temperature working environments, resulting in insufficient service stability and making it difficult to meet the reliability requirements of long-term high-temperature operation of equipment while ensuring that the basic magnetic properties remain unchanged.

[0004] To address the shortcomings of the existing technologies, there is an urgent need in this field to improve the material modification and matching schemes, adopt a multi-dimensional synergistic modification approach to optimize product performance, solve the defects of grain boundary softening at high temperatures and uneven distribution of single materials, improve the high-temperature stability and magnetic performance retention of NdFeB magnets, and adapt them to the high-temperature and harsh working scenarios of various high-end equipment. Summary of the Invention

[0005] The purpose of this invention is to provide a high-temperature resistant neodymium iron boron magnet and its preparation method, so as to solve the problems mentioned in the background art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a high-temperature resistant neodymium iron boron magnet includes the following steps: S1. Weigh 986-995 parts of NdFeB powder, 3-8 parts of boron-oxygen composite modified powder and 2-6 parts of layered composite oxide modified powder according to the mass fraction, place them in a vacuum drying environment of 80-100℃ for 2-4 hours, and then mix them at a speed of 300-500 r / min for 40-60 minutes under inert gas protection to obtain composite modified NdFeB mixed powder; S2. The composite modified NdFeB mixed powder is pressed into shape under an orientation magnetic field strength of 1.8-2.2T and a pressure of 8-12MPa. Then, it is pre-vented at 600-680℃ for 0.5-1h under vacuum conditions, and then heated to 1030-1080℃ and held for 2-3h. S3. After the heat preservation process is completed, the furnace is cooled. First, the temperature is lowered to 850-900℃ and held for 1-1.5 hours, then the temperature is lowered to 480-520℃ and held for 2-2.5 hours. Finally, the furnace is cooled to room temperature to obtain high-temperature resistant NdFeB magnet blank. S4. The obtained magnet blanks are successively ground, cut, and chamfered for precision machining. After ultrasonic cleaning and hot air drying, high-temperature resistant neodymium iron boron magnets are obtained.

[0007] Preferably, the preparation method of the boron-oxygen composite modified powder includes the following steps: S11. Weigh neodymium nitrate, dysprosium nitrate and boric acid in a mass ratio of 16.9-21.6:6.5-9.8:1.0, add them to deionized water and stir for 20-30 minutes. Then add borate microcrystalline modified powder and sodium citrate as a dispersant. Disperse the mixture by ultrasonication for 30-40 minutes to obtain a mixed solution. S12. Slowly add 0.5-0.8 mol / L ammonium bicarbonate precipitant to the mixture, adjust the pH of the system to 7.5-8.5, and stir the reaction at 55-65℃ for 2-3 hours to obtain the composite precipitate slurry. S13. Let the composite precipitate slurry stand for 4-6 hours to settle, filter and collect the solid precipitate product, and wash it with deionized water 3-5 times and anhydrous ethanol 1-2 times in sequence. S14. The washed solid product is dried at 80-100℃ for 8-12 hours, then calcined at 600-700℃ for 2-2.5 hours. After cooling in the furnace, it is ground and passed through a 300-400 mesh sieve to obtain boron-oxygen composite modified powder.

[0008] Preferably, the preparation method of the layered composite oxide modified powder includes the following steps: S21. Weigh praseodymium nitrate, cobalt nitrate and gallium nitrate in a mass ratio of 1:0.8-1.2:0.5-0.8, add them to deionized water and stir to dissolve, thus preparing a ternary metal salt solution; S22. Add urea to the ternary metal salt solution, stir continuously for 20-40 min, and then place it in a sealed environment to react at 110-130℃ for 10-14 h. S23. After the reaction is complete, cool naturally to room temperature, filter and collect the layered solid product, and wash it 3-4 times alternately with deionized water and anhydrous ethanol. Then dry the washed product at 70-90℃ for 10-14h. S24. Place the dried product in a muffle furnace and heat it to 500-600℃ at a heating rate of 3-5℃ / min. Hold it at this temperature for 2-3 hours. After cooling in the furnace, grind it through a 300-mesh sieve to obtain layered composite oxide modified powder.

[0009] Preferably, the method for preparing the borate microcrystalline modified powder includes the following steps: S111. Weigh terbium nitrate, zirconium nitrate and boric acid in a mass ratio of 1.84:0.65:1.0, add them to deionized water, stir evenly, then add sodium dodecylbenzenesulfonate and stir for 20-40 min. Then place it in a sealed environment and react at 170-190℃ for 8-10 h. S112. After the reaction is completed, the product is cooled and discharged, and the solid product is filtered and washed. The washed solid product is dried at 90-110℃ for 6-8 hours, then calcined at 550-600℃ for 1.5-2.5 hours, and finally cooled naturally and ultra-finely ground to obtain borate microcrystalline modified powder.

[0010] Preferably, the inert gas is high-purity argon; the density of the pressed product is 3.8-4.2 g / cm³.

[0011] Preferably, the amount of deionized water added is 10-15 times the total mass of neodymium nitrate, dysprosium nitrate and boric acid; The amount of borate microcrystalline modified powder added is 3%-8% of the total mass of neodymium nitrate, dysprosium nitrate and boric acid; The amount of sodium citrate added is 1%-3% of the total mass of neodymium nitrate, dysprosium nitrate and boric acid.

[0012] Preferably, the amount of deionized water added is 9-14 times the total mass of praseodymium nitrate, cobalt nitrate, and gallium nitrate; The amount of urea added is 40%-70% of the total mass of praseodymium nitrate, cobalt nitrate and gallium nitrate.

[0013] Preferably, the amount of deionized water added is 8-12 times the total mass of terbium nitrate, zirconium nitrate, and boric acid; The amount of sodium dodecylbenzenesulfonate added is 0.5%-1.5% of the total mass of terbium nitrate, zirconium nitrate and boric acid.

[0014] Preferably, the 0.5-0.8 mol / L ammonium bicarbonate precipitant is prepared by uniformly adding ammonium bicarbonate solid powder into deionized water under normal temperature and pressure conditions, and continuously stirring until the solid is completely dissolved.

[0015] A high-temperature resistant neodymium iron boron magnet was prepared by the above-described preparation method.

[0016] Compared with the prior art, the beneficial effects of the present invention are: This invention employs a synergistic blend of layered composite oxide modified powder and boron-oxygen composite modified powder to effectively improve the defects of traditional NdFeB magnets, such as poor high-temperature stability and uneven material mixing. The layered composite oxide modified powder, after high-temperature calcination and dehydroxylation, possesses a stable porous layered structure and high specific surface area. During the mixing stage, it can effectively promote the uniform dispersion of the boron-oxygen composite modified powder in the NdFeB matrix powder through surface adsorption, improving the wettability and contact uniformity between the component particles. During sintering, the boron-oxygen composite modified powder is uniformly distributed in the grain boundary region, significantly optimizing the magnet's grain boundary structure, enhancing grain boundary stability, and effectively suppressing magnetic domain flipping and grain deterioration behavior at high temperatures.

[0017] Through multi-component synergistic optimization, it achieves the beneficial effects of significantly improving high-temperature coercivity, reducing high-temperature irreversible magnetic loss, and enhancing thermal stability and thermal shock resistance. It greatly improves the stability and service life under harsh conditions of high temperature and high load, and is suitable for the use of new energy vehicle drive motors, high-temperature servo motors and industrial high-temperature permanent magnet devices. Attached Figure Description

[0018] Figure 1 This is a flowchart illustrating the manufacturing process of the high-temperature resistant NdFeB magnet of the present invention. Figure 2 This is a flow chart of the preparation process of the boron-oxygen composite modified powder of the present invention; Figure 3 This is a process flow diagram for preparing the layered composite oxide modified powder of the present invention; Figure 4 This is a flow chart of the preparation process of the borate microcrystalline modified powder of the present invention. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] Please see Figures 1-4 The present invention provides a technical solution: Example 1 Before preparing high-temperature resistant NdFeB magnets, borate microcrystalline modified powder, boron-oxygen composite modified powder, and layered composite oxide modified powder are prepared first: (I) A method for preparing borate microcrystalline modified powder, comprising the following steps: S111 Weigh 18.4g terbium nitrate, 6.5g zirconium nitrate and 10g boric acid, add them to 279.2g deionized water, stir well, then add 0.175g sodium dodecylbenzenesulfonate and stir for 20min. Place in a sealed environment and react at 170℃ for 8h. S112. After the reaction is completed, the material is cooled and discharged, and the solid product is filtered and washed. The washed solid product is dried at 90°C for 6 hours, then calcined at 550°C for 1.5 hours, and finally cooled naturally and ultra-finely ground to obtain borate microcrystalline modified powder.

[0021] (II) A method for preparing boron-oxygen composite modified powder, comprising the following steps: S11. Weigh 169g neodymium nitrate, 65g dysprosium nitrate and 10g boric acid, add to 2440g deionized water and stir for 20min, then add 7.32g borate microcrystalline modified powder and 2.44g sodium citrate as dispersant, and ultrasonically disperse for 30min to obtain a mixture. S12. Slowly add 0.5 mol / L ammonium bicarbonate precipitant to the mixture (preparation of 0.5 mol / L ammonium bicarbonate precipitant: under normal temperature and pressure conditions, weigh 39.5 g of ammonium bicarbonate solid powder, add it uniformly to 1000 mL of deionized water, and stir continuously until the solid is completely dissolved), adjust the pH value of the system to 7.5, and stir the reaction at 55℃ for 2 h to obtain the composite precipitate slurry; S13. Let the composite precipitate slurry stand for 4 hours to settle, filter and collect the solid precipitate product, and wash it with deionized water 3 times and anhydrous ethanol once in sequence. S14. The washed solid product is dried at 80°C for 8 hours, then calcined at 600°C for 2 hours. After cooling in the furnace, it is ground and passed through a 300-mesh sieve to obtain boron-oxygen composite modified powder.

[0022] (III) A method for preparing layered composite oxide modified powder, comprising the following steps: S21. Weigh 37.7g of praseodymium nitrate, 30.16g of cobalt nitrate and 18.85g of gallium nitrate, and add them to 780.39g of deionized water and stir to dissolve, thus preparing a ternary metal salt solution; S22. Add 34.684g of urea to the ternary metal salt solution, stir continuously for 20min, and then place it in a sealed environment to react at 110℃ for 10h. S23. After the reaction is complete, the product is naturally cooled to room temperature, filtered and collected as a layered solid. The product is then washed three times with deionized water and anhydrous ethanol, and then dried at 70°C for 10 hours. S24. Place the dried product in a muffle furnace and heat it to 500°C at a heating rate of 3°C / min. Hold it at this temperature for 2 hours and then grind it through a 300-mesh sieve after cooling in the furnace to obtain layered composite oxide modified powder.

[0023] This embodiment provides a method for preparing a high-temperature resistant neodymium iron boron magnet, including the following steps: S1. Weigh 986g of NdFeB powder, 3g of boron-oxygen composite modified powder and 2g of layered composite oxide modified powder, place them in an environment of 80℃ for vacuum drying for 2h, and then mix them at a speed of 300r / min for 40min under the protection of high-purity argon to obtain composite modified NdFeB mixed powder. S2. The composite modified NdFeB mixed powder was pressed into shape under an orientation magnetic field strength of 1.8T and a pressure of 8MPa (pressing density of 3.8g / cm³), and then pre-vented at 600℃ for 0.5h under vacuum conditions, and then heated to 1030℃ and held for 2h. S3. After the heat preservation process is completed, the furnace is cooled. First, the temperature is lowered to 850℃ and kept for 1 hour, then lowered to 480℃ and kept for 2 hours, and finally cooled to room temperature in the furnace to obtain high temperature resistant NdFeB magnet blank. S4. The obtained magnet blanks are successively ground, cut, and chamfered for precision machining. After ultrasonic cleaning and hot air drying, high-temperature resistant neodymium iron boron magnets are obtained.

[0024] Example 2 Before preparing high-temperature resistant NdFeB magnets, borate microcrystalline modified powder, boron-oxygen composite modified powder, and layered composite oxide modified powder are prepared first: (I) A method for preparing borate microcrystalline modified powder, comprising the following steps: S111. Weigh 18.4g of terbium nitrate, 6.5g of zirconium nitrate and 10g of boric acid, add them to 418.8g of deionized water, stir well, then add 0.524g of sodium dodecylbenzenesulfonate and stir for 40min. Then place it in a sealed environment and react at 190℃ for 10h. S112. After the reaction is completed, the product is cooled and discharged, and the solid product is filtered and washed. The washed solid product is dried at 110℃ for 8 hours, then calcined at 600℃ for 2.5 hours, and finally cooled naturally and ultra-fine ground to obtain borate microcrystalline modified powder.

[0025] (II) A method for preparing boron-oxygen composite modified powder, comprising the following steps: S11. Weigh 216g neodymium nitrate, 98g dysprosium nitrate and 10g boric acid, add to 4860g deionized water and stir for 30min, then add 25.92g borate microcrystalline modified powder and 9.72g sodium citrate as dispersant, and ultrasonically disperse for 40min to obtain a mixture. S12. Slowly add 0.8 mol / L ammonium bicarbonate solution to the mixture (preparation of 0.8 mol / L ammonium bicarbonate precipitant: under normal temperature and pressure conditions, weigh 63.2 g of ammonium bicarbonate solid powder, add it uniformly to 1000 mL of deionized water, and stir continuously until the solid is completely dissolved), adjust the pH value of the system to 8.5, and stir the reaction at 65℃ for 3 h to obtain composite precipitate slurry; S13. Let the composite precipitate slurry stand for 6 hours to settle, filter and collect the solid precipitate product, and wash it with deionized water 5 times and anhydrous ethanol 2 times in sequence. S14. The washed solid product is dried at 100℃ for 12 hours, then calcined at 700℃ for 2.5 hours. After cooling in the furnace, it is ground and passed through a 400-mesh sieve to obtain boron-oxygen composite modified powder.

[0026] (III) A method for preparing layered composite oxide modified powder, comprising the following steps: S21. Weigh 40g of praseodymium nitrate, 48g of cobalt nitrate and 32g of gallium nitrate, and add them to 1680g of deionized water and stir to dissolve them to prepare a ternary metal salt solution. S22. Add 84g of urea to the ternary metal salt solution, stir continuously for 40min, and then place it in a sealed environment to react at 130℃ for 14h. S23. After the reaction is complete, the product is naturally cooled to room temperature, filtered and collected as a layered solid. The product is then washed four times with deionized water and anhydrous ethanol, and then dried at 90°C for 14 hours. S24. Place the dried product in a muffle furnace and heat it to 600°C at a heating rate of 5°C / min. Maintain this temperature for calcination for 3 hours. After cooling in the furnace, grind the product through a 300-mesh sieve to obtain layered composite oxide modified powder. This embodiment provides a method for preparing high-temperature resistant NdFeB magnets, including the following steps: S1. Weigh 995g of NdFeB powder, 8g of boron-oxygen composite modified powder and 6g of layered composite oxide modified powder, place them in a vacuum dryer at 100℃ for 4h, and then mix them at 500r / min for 60min under high-purity argon protection to obtain composite modified NdFeB mixed powder. S2. The composite modified NdFeB mixed powder was pressed into shape under a magnetic field strength of 2.2T and a pressure of 12MPa (pressing density of 4.2g / cm³), and then pre-vented at 680℃ for 1h under vacuum conditions, and then heated to 1080℃ and held for 3h. S3. After the heat preservation process is completed, the furnace is cooled down to 900℃ and kept at that temperature for 1.5 hours, then cooled down to 520℃ and kept at that temperature for 2.5 hours, and finally cooled down to room temperature in the furnace to obtain a high-temperature resistant NdFeB magnet blank. S4. The obtained magnet blanks are successively ground, cut, and chamfered for precision machining. After ultrasonic cleaning and hot air drying, high-temperature resistant neodymium iron boron magnets are obtained.

[0027] Example 3 Before preparing high-temperature resistant NdFeB magnets, borate microcrystalline modified powder, boron-oxygen composite modified powder, and layered composite oxide modified powder are prepared first: (I) A method for preparing borate microcrystalline modified powder, comprising the following steps: S111 Weigh 18.4g terbium nitrate, 6.5g zirconium nitrate and 10g boric acid, add to 349g deionized water, stir well, then add 0.349g sodium dodecylbenzenesulfonate and stir for 30min. Place in a sealed environment and react at 180℃ for 9h. S112. After the reaction is completed, the material is cooled and discharged, and the solid product is filtered and washed. The washed solid product is dried at 100℃ for 7 hours, then calcined at 575℃ for 2 hours, and finally cooled naturally and ultra-finely ground to obtain borate microcrystalline modified powder.

[0028] (II) A method for preparing boron-oxygen composite modified powder, comprising the following steps: S11. Weigh 192.5g neodymium nitrate, 81.5g dysprosium nitrate and 10g boric acid, add them to 3550g deionized water and stir for 25min. Then add 15.62g borate microcrystalline modified powder and 5.68g sodium citrate as a dispersant. Disperse the mixture by ultrasonication for 35min to obtain a mixture. S12. Slowly add 0.65 mol / L ammonium bicarbonate solution to the mixture (preparation of 0.65 mol / L ammonium bicarbonate precipitant: under normal temperature and pressure conditions, weigh 51.4 g of ammonium bicarbonate solid powder, add it uniformly to 1000 mL of deionized water, and stir continuously until the solid is completely dissolved), adjust the pH of the system to 8.0, and stir the reaction at 60℃ for 2.5 h to obtain the composite precipitate slurry; S13. Let the composite precipitate slurry stand for 5 hours to settle, filter and collect the solid precipitate product, and wash it with deionized water 4 times and anhydrous ethanol 2 times in sequence. S14. The washed solid product is dried at 90℃ for 10 hours, then calcined at 650℃ for 2 hours, cooled in the furnace, ground and passed through a 350-mesh sieve to obtain boron-oxygen composite modified powder.

[0029] (III) A method for preparing layered composite oxide modified powder, comprising the following steps: S21. Weigh 40g of praseodymium nitrate, 40g of cobalt nitrate and 26g of gallium nitrate, and add them to 1219g of deionized water and stir to dissolve them to prepare a ternary metal salt solution. S22. Add 58.3g of urea to the ternary metal salt solution, stir continuously for 30min, and then place in a sealed environment to react at 120℃ for 12h. S23. After the reaction is complete, the product is naturally cooled to room temperature, filtered and collected as a layered solid. The product is then washed four times with deionized water and anhydrous ethanol, and then dried at 80°C for 12 hours. S24. Place the dried product in a muffle furnace and heat it to 550°C at a heating rate of 4°C / min. Maintain this temperature for 2.5 hours and calcine. After cooling in the furnace, grind the product through a 300-mesh sieve to obtain layered composite oxide modified powder. This embodiment provides a method for preparing high-temperature resistant NdFeB magnets, including the following steps: S1. Weigh 990.5g of NdFeB powder, 5.5g of boron-oxygen composite modified powder and 4.0g of layered composite oxide modified powder, place them in a vacuum dryer at 90℃ for 3h, and then mix them at 400r / min for 50min under high-purity argon protection to obtain composite modified NdFeB mixed powder. S2. The composite modified NdFeB mixed powder is pressed into shape under a magnetic field strength of 2.0T and a pressure of 10MPa (pressing density is 4.0g / cm³), and then pre-vented at 640℃ for 0.5h under vacuum conditions, and then heated to 1055℃ and held for 2.5h. S3. After the heat preservation process is completed, the furnace is cooled down to 880℃ and kept for 1 hour, then cooled down to 500℃ and kept for 2 hours, and finally cooled down to room temperature to obtain high temperature resistant NdFeB magnet blank. S4. The obtained magnet blanks are successively ground, cut, and chamfered for precision machining. After ultrasonic cleaning and hot air drying, high-temperature resistant neodymium iron boron magnets are obtained.

[0030] Comparative Example 1 The difference between this comparative example and Example 3 is that no layered composite oxide modified powder is added in step S1, while the remaining raw material ratios, modified powder preparation methods and process steps are exactly the same as in Example 3.

[0031] Comparative Example 2 The difference between this comparative example and Example 3 is that no boron-oxygen composite modified powder is added in step S1, while the remaining raw material ratios, modified powder preparation methods and process steps are exactly the same as in Example 3.

[0032] Comparative Example 3 The difference between this comparative example and Example 3 is that neither layered composite oxide modified powder nor boron-oxygen composite modified powder is added in step S1. The remaining raw material ratios, modified powder preparation methods and process steps are exactly the same as in Example 3.

[0033] Performance Testing and Result Analysis The high-temperature resistant neodymium iron boron magnets obtained in Examples 1-3 and Comparative Examples 1-3 were processed into standard test samples (size: Φ10mm×10mm) and subjected to the following performance tests: (1) Room temperature and high temperature coercivity test: Referring to GB / T 3217-2013 "Magnetic Test Method for Permanent Magnet (Hard Magnet) Materials" and GB / T 13560-2017 "Sintered NdFeB Permanent Magnet Materials", the initial coercivity (Hcj) of the sample was tested at room temperature of 20℃ using a closed magnetic circuit permanent magnet measuring device. Then the sample was saturated with magnets, placed in a constant temperature environment of 150℃ for 2 hours, and then cooled to room temperature before the coercivity was tested again.

[0034] (2) High temperature irreversible magnetic loss test: Refer to GB / T 40794-2021 "Method for measuring irreversible magnetic flux loss of permanent magnet materials at high temperature", saturate the sample with magnetization at room temperature and test the initial open circuit magnetic flux (Φ0); then place it in a constant temperature chamber at 150℃ for 2 hours, take it out and let it cool naturally to room temperature, and test its open circuit magnetic flux (Φ1) again.

[0035] (3) Thermal stability test (Curie temperature): Referring to GB / T 43870.1-2024 "Method for measuring Curie temperature of magnetic materials", the magnetization intensity-temperature (MT) curve of the sample is tested using a vibrating sample magnetometer (VSM). The Curie temperature (Tc) of the magnet is determined by the tangent method, thereby characterizing the upper limit of the thermal stability of the material.

[0036] (4) Thermal shock resistance test: Following the high-temperature stability test principles in GB / T 13560-2017 "Sintered NdFeB Permanent Magnet Materials" and the method of "Test Na: Temperature Change at a Specified Conversion Time" in GB / T 2423.22-2012 "Environmental Testing Part 2: Test Methods Test N: Temperature Change", the test was conducted in a dry air environment. The saturated magnetized sample underwent a thermal shock cycle test. The specific steps were as follows: the sample was placed in an environment of 150℃ for 30 minutes, then quickly removed and placed in room temperature deionized water to cool to room temperature. This constituted one cycle. After 50 consecutive thermal shock cycles, its coercivity was tested, and the attenuation rate was calculated.

[0037] Table 1: Performance Test Results Analysis of Table 1 shows that without the addition of layered composite oxide modified powder (Comparative Example 1), the coercivity retention rate at 150℃ drops sharply to 82.5%, the irreversible magnetic loss at 150℃ increases to 4.5%, and the coercivity decay rate after 50 thermal shocks rises to 5.8%, confirming that the layered composite oxide modified powder can effectively buffer severe thermal stress to ensure the integrity of the magnet structure. Without the use of boron-oxygen composite modified powder (Comparative Example 2), the coercivity retention rate at 150℃ drops to 75.6%, the irreversible magnetic loss at 150℃ surges to 6.2%, and the Curie temperature drops to 298℃, confirming the effectiveness of the boron-oxygen composite modified powder. Enhancing grain boundary stability and synergistically suppressing high-temperature magnetic domain flipping and grain boundary softening; without the addition of layered composite oxide modified powder or boron-oxygen composite modified powder (Comparative Example 3), the coercivity retention rate at 150℃ was only 65.2%, the irreversible magnetic loss at 150℃ was as high as 9.8%, the Curie temperature dropped to 290℃, and the coercivity decay rate after 50 thermal shocks surged to 14.2%. This verifies that the multi-level synergistic effect of layered composite oxide modified powder and boron-oxygen composite modified powder is the core key to endowing NdFeB magnets with excellent high-temperature coercivity, extremely low irreversible magnetic loss, excellent thermal stability, and thermal shock resistance.

[0038] In summary, this invention, through multi-component synergistic optimization, achieves the beneficial effects of significantly improving high-temperature coercivity, reducing high-temperature irreversible magnetic loss, and enhancing thermal stability and thermal shock resistance. It greatly improves the stability and service life under harsh conditions of high temperature and high load, and is perfectly suited to the application requirements of new energy vehicle drive motors, high-temperature servo motors, and industrial high-temperature permanent magnet devices.

[0039] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-temperature resistant neodymium iron boron magnet, characterized in that, Includes the following steps: S1. Weigh 986-995 parts of NdFeB powder, 3-8 parts of boron-oxygen composite modified powder and 2-6 parts of layered composite oxide modified powder according to the mass fraction, place them in a vacuum drying environment of 80-100℃ for 2-4 hours, and then mix them at a speed of 300-500 r / min for 40-60 minutes under inert gas protection to obtain composite modified NdFeB mixed powder; S2. The composite modified NdFeB mixed powder is pressed into shape under an orientation magnetic field strength of 1.8-2.2T and a pressure of 8-12MPa. Then, it is pre-vented at 600-680℃ for 0.5-1h under vacuum conditions, and then heated to 1030-1080℃ and held for 2-3h. S3. After the heat preservation process is completed, the furnace is cooled. First, the temperature is lowered to 850-900℃ and held for 1-1.5 hours, then the temperature is lowered to 480-520℃ and held for 2-2.5 hours. Finally, the furnace is cooled to room temperature to obtain high-temperature resistant NdFeB magnet blank. S4. The obtained magnet blanks are successively ground, cut, and chamfered for precision machining. After ultrasonic cleaning and hot air drying, high-temperature resistant neodymium iron boron magnets are obtained.

2. A method for preparing a high-temperature resistant NdFeB magnet according to claim 1, characterized in that, The preparation method of the boron-oxygen composite modified powder includes the following steps: S11. Weigh neodymium nitrate, dysprosium nitrate and boric acid in a mass ratio of 16.9-21.6:6.5-9.8:1.0, add them to deionized water and stir for 20-30 minutes. Then add borate microcrystalline modified powder and sodium citrate as a dispersant. Disperse the mixture by ultrasonication for 30-40 minutes to obtain a mixed solution. S12. Slowly add 0.5-0.8 mol / L ammonium bicarbonate precipitant to the mixture, adjust the pH of the system to 7.5-8.5, and stir the reaction at 55-65℃ for 2-3 hours to obtain the composite precipitate slurry. S13. Let the composite precipitate slurry stand for 4-6 hours to settle, filter and collect the solid precipitate product, and wash it with deionized water 3-5 times and anhydrous ethanol 1-2 times in sequence. S14. The washed solid product is dried at 80-100℃ for 8-12 hours, then calcined at 600-700℃ for 2-2.5 hours. After cooling in the furnace, it is ground and passed through a 300-400 mesh sieve to obtain boron-oxygen composite modified powder.

3. A method for preparing a high-temperature resistant NdFeB magnet according to claim 1, characterized in that, The preparation method of the layered composite oxide modified powder includes the following steps: S21. Weigh praseodymium nitrate, cobalt nitrate and gallium nitrate in a mass ratio of 1:0.8-1.2:0.5-0.8, add them to deionized water and stir to dissolve, thus preparing a ternary metal salt solution; S22. Add urea to the ternary metal salt solution, stir continuously for 20-40 min, and then place it in a sealed environment to react at 110-130℃ for 10-14 h. S23. After the reaction is complete, cool naturally to room temperature, filter and collect the layered solid product, and wash it 3-4 times alternately with deionized water and anhydrous ethanol. Then dry the washed product at 70-90℃ for 10-14h. S24. Place the dried product in a muffle furnace and heat it to 500-600℃ at a heating rate of 3-5℃ / min. Hold it at this temperature for 2-3 hours. After cooling in the furnace, grind it through a 300-mesh sieve to obtain layered composite oxide modified powder.

4. A method for preparing a high-temperature resistant NdFeB magnet according to claim 2, characterized in that, The method for preparing the borate microcrystalline modified powder includes the following steps: S111. Weigh terbium nitrate, zirconium nitrate and boric acid in a mass ratio of 1.84:0.65:1.0, add them to deionized water, stir evenly, then add sodium dodecylbenzenesulfonate and stir for 20-40 min. Then place it in a sealed environment and react at 170-190℃ for 8-10 h. S112. After the reaction is completed, the product is cooled and discharged, and the solid product is filtered and washed. The washed solid product is dried at 90-110℃ for 6-8 hours, then calcined at 550-600℃ for 1.5-2.5 hours, and finally cooled naturally and ultra-finely ground to obtain borate microcrystalline modified powder.

5. A method for preparing a high-temperature resistant NdFeB magnet according to claim 1, characterized in that, The inert gas is high-purity argon; the density of the pressed product is 3.8-4.2 g / cm³.

6. A method for preparing a high-temperature resistant neodymium iron boron magnet according to claim 2, characterized in that, The amount of deionized water added is 10-15 times the total mass of neodymium nitrate, dysprosium nitrate and boric acid; The amount of borate microcrystalline modified powder added is 3%-8% of the total mass of neodymium nitrate, dysprosium nitrate and boric acid; The amount of sodium citrate added is 1%-3% of the total mass of neodymium nitrate, dysprosium nitrate and boric acid.

7. A method for preparing a high-temperature resistant neodymium iron boron magnet according to claim 3, characterized in that, The amount of deionized water added is 9-14 times the total mass of praseodymium nitrate, cobalt nitrate, and gallium nitrate; The amount of urea added is 40%-70% of the total mass of praseodymium nitrate, cobalt nitrate and gallium nitrate.

8. A method for preparing a high-temperature resistant neodymium iron boron magnet according to claim 4, characterized in that, The amount of deionized water added is 8-12 times the total mass of terbium nitrate, zirconium nitrate and boric acid; The amount of sodium dodecylbenzenesulfonate added is 0.5%-1.5% of the total mass of terbium nitrate, zirconium nitrate and boric acid.

9. A method for preparing a high-temperature resistant neodymium iron boron magnet according to claim 2, characterized in that, Preparation of the 0.5-0.8 mol / L ammonium bicarbonate precipitant: Under normal temperature and pressure conditions, ammonium bicarbonate solid powder is added to deionized water at a uniform speed and stirred continuously until the solid is completely dissolved.

10. A high-temperature resistant neodymium iron boron magnet, characterized in that, The high-temperature resistant neodymium iron boron magnet is prepared by the preparation method according to any one of claims 1 to 9.